Adapting to change: exploring the distribution dynamics of the alien and potentially invasive aphid species Cinara curvipes (Hemiptera: Aphididae) in the context of global warming - K. Wieczorek; A. Bugaj-Nawrocka; B. Borowiak-Sobkowiak; A. Endrestøl; H. P. Ravn; W. Solarz; R. Durak (The European Zoological Journal)
This study investigates the potential ecological niche and distribution of the Nearctic bow-legged fir aphid, Cinara curvipes, an alien and potentially invasive species, across Europe. Utilising climate modelling based on climatic preferences in its native range, we assess the suitability of European climates for facilitating the spread of this aphid. Coupled with the presence of suitable host plants, mostly firs (Abies spp.) or cedars (Cedrus spp.), there is potential for the bow-legged fir aphid to extend its range across most European regions, with projections suggesting potential expansion into Asia Minor. Furthermore, future climate scenarios predict a northward expansion of suitable habitats for this aphid species, confirmed by its detection in Denmark and Norway. Our research reveals that C. curvipes displays notably higher fecundity compared to its Cinara genus counterparts. Specifically, wingless viviparous females of this species achieve peak fecundity at lower temperatures (10–15°C), explaining their spring mass appearances. At 25°C, nymphs fail to moult or reach maturity, leading to summer population declines. Unique survival mechanisms, including the production of numerous winged morphs under overcrowded conditions, enable rapid dispersal facilitated by human-mediated transport, notably through the “Christmas trees” trade. Its high reproductive output allows the species to quickly colonise new habitats and exploit available resources, contributing to its potential invasiveness. We emphasise the critical need for collaborative engagement among researchers, stakeholders, and the public to bolster citizen science initiatives and reinforce environmental monitoring networks, all within the framework of an early detection and rapid response (EDRR) process. This collaborative approach is vital for effective environmental management and mitigating potential invasive threats.